MUSE sneaks a peek at extreme ram-pressure stripping events – IV. Hydrodynamic and gravitational interactions in the Blue Infalling Group. Issue 2 (12th January 2019) - Fossati, Matteo; Fumagalli, Michele; Gavazzi, Giuseppe; Consolandi, Guido; Boselli, Alessandro; Yagi, Masafumi; Sun, Ming; Wilman, David J
Abstract: We report new wide-field (≈4 × 4 arcmin 2 ) Multi Unit Spectroscopic Explorer (MUSE) observations of the Blue Infalling Group (BIG), a compact group of galaxies located at a projected distance of ≃150 kpc from the X-ray centre of the A1367 cluster at $z$ = 0.021. Our MUSE observations map in detail the extended ionized gas, primarily traced by H α emission, in between the members of the group. The gas morphology and its kinematics appear consistent with a tidal origin due to galaxy encounters, as also supported by the disturbed kinematics visible in one of the group members and the presence of tidal dwarf systems. A diffuse tail extending in the direction opposite to the cluster centre is also detected, hinting at a global ram-pressure stripping of the intragroup material as BIG falls inside A1367. Based on the analysis of spatially resolved emission line maps, we identify multiple ionization mechanisms for the diffuse gas filaments, including in situ photoionization from embedded H ii regions and shocks. Combining spatially resolved kinematics and line ratios, we rule out the association of the most massive galaxy, CGCG097-120, with the group as this system appears to be decoupled from the intragroup medium and subject to strong ram pressure as it falls into A1367. Through our new analysis, we conclude that BIG is shaped by pre-processing produced by gravitational interactions in the Local Group environment combined with ram-pressure stripping by the global cluster halo.